Strengthening The Profil Pelajar Pancasila Through Project Citizen: A Case Study at SMP Negeri 21 Semarang - Masrukhi, Masrukhi; Wijayanti, Tutik; Pramono, Didi; Irawan, Hendri; Kurniawan, Muhammad Andi (IJTIMAIYA: Journal of Social Science and Teaching, 2024)
This study has the main objective in internalizing the Pancasila Student Profile, namely Indonesian students as lifelong learners who have global competence and behave in accordance with the ethics, character, and values of Pancasila. The Pancasila Student Profile has six main characteristics, namely, faith, devotion to God Almighty, and noble character, global diversity, mutual cooperation, independence, critical thinking, and creativity at SMP N 21 Semarang. These six characteristics are strategically arranged which are oriented towards improving the quality of Indonesian human resources while adhering to cultural progress that reflects the personality of the nation through clean, effective and trusted governance. This study uses a qualitative approach method with data collection techniques obtained through observation, interviews, documentation and literature studies. Data analysis was carried out using the Miles and Huberman interactive analysis model. The data validity checking technique uses source triangulation. The results of this study indicate that, in realizing Pancasila students, it can be attempted in various ways, one of which is through the citizen project as an effort to strengthen the Pancasila student profile. Project citizen is a problem-based instructional treatment to optimize the affective, cognitive, and psychomotor dimensions, social awareness attitudes, citizenship character, and encourage student participation in solving socio-cultural problems that occur in society. Project Citizen is a positive activity, and also supports students in building their character and good behavior in accordance with the mandate of the Pancasila values reflected in all aspects of life.